ANALYSIS OF BOUND INFLECTIONAL AND DERIVATIONAL IN A SHORT STORY THE WAR OF THE WORDS BY H.G WELLS - Randa Yustika; Zuhri Efendi (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyze the inflexional and derivative bound morphemes in the short story The War of the Words by H.G. Wells. This study uses a literature-based qualitative descriptive method, with data obtained through reading and note-taking techniques. The analysis shows that inflectional affixes as much as 10.52% (-s, -es, -ed, -er, -est and -ing) and the second derivational affixes as much as 5.78% (-ment, -ness, -ity, -al, -ance, -ence, -ship, -dom, -er, -or, -ist, -ian, -ize, -ify, -ful, -less, -able, -ible, -ous, -ive), produce new words with changes in grammatical category and meaning. Both types of morphemes were found in equal numbers in the analyzed texts. The findings of this study provide insights into how morpheme structure and function affect word formation in English. This understanding is important for vocabulary development, language learning and linguistic analysis. In addition, this study supports the teaching of morphological concepts by providing concrete examples from literary texts.